DePFET—Recent Developments and Future Prospects - Andricek, Ladislav; Bähr, Alexander; Lechner, Peter; Ninkovic, Jelena; Richter, Rainer; Schopper, Florian; Treis, Johannes (Frontiers in Physics, 2022)
The DePFET is a sensor amplifier structure first proposed in 1987. In recent years, DeFPET based sensors have been deployed for particle physics at Belle II and been launched into space aboard the planetary science mission BepiColombo in its MIXS instrument. In the future DePFETs are proposed for the WFI aboard the Athena satellite and developed for use as real-time imager for transmission electron microscopes. These sensors have all been tailored to the needs of the respective application, providing high frame rates and accurate position resolution for particle tracking, Fano-limited energy resolution and position resolution matched to telescopes for X-ray spectroscopy or high frame rates and maximized dynamic range for applications on TEMs. In addition to this, several DePFET based concepts, implementing additional functionality on pixel level have been tested in recent years. Among these are the tailoring of the internal gates shape to implement a non-linear signal response and provide a larger dynamic range or a drastic increase of the DePFETs amplification. Furthermore, "super pixels" providing capabilities to reach sub electron noise and single electron resolution, a fast electronic shutter on pixel level and the realization of multiple storage regions within one pixel have been tested. It was further demonstrated, that combinations of these features can also be realized. Over all, the development of the DePFET shows, that this is an ongoing process providing optimized sensors tailored to the need of a specific application.